Characterization of AMI hospitalization and mortality in pandemic times, analysis of 2018-2022, in Brazil - Oliveira, Daiane Pereira (2022)
Cardiovascular Diseases (CVD) are the main cause of general mortality in Brazil and in the world, among which the Acute Myocardial Infarction (AMI) stands out, but a new scenario of lethality in patients infected with Sars-cov-02 has become the focus of care for all hospitals worldwide. This study aimed to characterize the hospitalization and mortality due to AMI in pandemic times in the comparison between 2018 and 2022. This is a cross-sectional, descriptive and quantitative study, which used SINAN/DATASUS as a data source. In the studied period, there were 615,145 hospitalizations and 60,134 deaths due to AMI. There was a decline in hospitalization numbers in 2020, with 19.72% re-establishing an increase in 2021, corresponding (23.52%) to maintaining a percentage increase in 2022.  Regarding the sociodemographic profile: 391,747 (63.7%) were male (86.11%) aged > 50 years, white (39.8%) and brown (33.2%). Deaths due to AMI: 2020 (19.07%) and 2021 (22.7%). The sociodemographic profile of deaths is similar to the profile of hospitalizations, the majority being male (56.1%), white and brown race, 38.73% and 31.45%, respectively, age group >70 years (52.48%). It is understood that the impacts of the pandemic may have greater consequences in the post-pandemic period with silent and masked complications, the postponement of preventive medical care, postponements of primary elective surgeries for patients with CVD. It is expected that the results of this research will contribute to the professional improvement of the epidemiological and sociodemographic profile with health actions aimed at the general population and those with greater vulnerability and susceptibility to the disease.